Penyuluhan Hukum mengenai Pencegahan Narkoba di SMPN 1 Kopo untuk Meningkatkan Kesadaran Siswa - Ridho Ilhami; Heni Hardiyanti; Aryo Pambudi; Siti Hanan; Lucky Setiawan; Doto Doto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Drug abuse among Indonesian teenagers continues to rise and poses a significant challenge to the development of the nation's future generation. Limited knowledge about legal and health issues makes students vulnerable to the negative impacts of narcotics. This initiative aims to provide legal education and information on the medical effects of drugs to students at SMPN 1 Kopo, Garut. The outreach program was conducted face-to-face using an interactive approach, including presentations, educational videos, and two-way discussions. The results showed an increase in student participation and understanding of the dangers of drugs, as well as legal awareness. This activity demonstrates that a collaborative educational approach can build resilience among teenagers in facing environmental pressures and encourage the creation of change agents within the school environment. The program is expected to serve as the first step toward long-term collaboration between educational institutions, law enforcement agencies, and the community in preventive anti-drug efforts. It is hoped that with closer collaboration, the younger generation will be better educated and protected from the dangers of drugs, and will contribute to creating a healthier, drug-free environment. This program is also a model that can be applied in other schools as part of a broader effort to prevent drug abuse within the community. By strengthening the understanding of legal consequences and health risks, this program can also act as a preventive measure, fostering a safer environment for students and promoting greater community engagement in combating drug-related issues, ensuring a sustainable impact on the community’s future. It is essential for such initiatives to be continuously reinforced and expanded to reach more schools and communities, thereby creating a more extensive network of awareness and prevention.